2011
DOI: 10.1007/s00011-011-0390-x
|View full text |Cite
|
Sign up to set email alerts
|

Di-(2-ethylhexyl) phthalate induces production of inflammatory molecules in human macrophages

Abstract: DEHP enhances the production of inflammatory cytokines and chemokines by macrophages, and exacerbates their inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 43 publications
(42 reference statements)
5
54
0
1
Order By: Relevance
“…In addition, KC/GRO has been hypothesized to be involved in germ cell proliferation, due to its role as a growth stimulator in certain cells such as human umbilical vein endothelial cells and melanocytes (Aubry et al 2000). Consistent with the current study, short term DEHP exposure (3 hours) has been shown to upregulate gene expression of KC in human macrophage-like THP-1 cells in vitro (Nishioka et al 2012). Similarly, 3 hours after DBP exposure (500mg/kg), Johnson, et al observed increased KC gene expression in rat testis in vivo (Johnson et al 2007).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, KC/GRO has been hypothesized to be involved in germ cell proliferation, due to its role as a growth stimulator in certain cells such as human umbilical vein endothelial cells and melanocytes (Aubry et al 2000). Consistent with the current study, short term DEHP exposure (3 hours) has been shown to upregulate gene expression of KC in human macrophage-like THP-1 cells in vitro (Nishioka et al 2012). Similarly, 3 hours after DBP exposure (500mg/kg), Johnson, et al observed increased KC gene expression in rat testis in vivo (Johnson et al 2007).…”
Section: Discussionsupporting
confidence: 90%
“…These markers are associated with antigen processing and presentation and cytokine–cytokine receptor interaction in immune cells. Similar increases in inflammatory marker expression have been reported after DEHP and MEHP treatment in different monocyte/macrophage models, such as the macrophage RAW264.7 cell line, 37 human acute monocytic leukemia THP-1 cell line 38 and rat alveolar macrophages. 39 Moreover, MEHP increases IL-5 and IL-10 levels in cultures of local lymph node cells, suggesting that phthalates activate the adaptive immune system.…”
Section: Discussionsupporting
confidence: 77%
“…Some phthalates have also been shown to induce proinflammatory cytokine release in cell lines (Jepsen et al 2004; Nishioka et al 2012) and have been linked to increased systemic levels of inflammatory markers such as C-reactive protein in humans (Ferguson et al 2011). Our data support this mechanism, as for spontaneous preterm births we saw the strongest associations with phthalate metabolites measured in third trimester urine samples.…”
Section: Discussionmentioning
confidence: 99%